Comparative analysis of the liquidity ratios of the largest banks of Serbia: Indicator of performance measurement - Vesić, Tamara; Ravić, Nenad; Đekić, Maja (Anali Ekonomskog fakulteta u Subotici, 2020)
Under the influence of globalization, there are changes in regulation and liberalization of the movement of people and capital, the trend of modification and modernization of the way banks operate. In this paper we analyzed the liquidity of ten largest banks in the Republic of Serbia according to the balance sheet assets for the period from 2010 to 2017, with the aim to see why oscillations in liquidity indicators occur. The subject of research in this paper is a comparative analysis of the ratio of liquidity indicators, with a review of the movement of the reference interest rate and the movement of non-performing loans, and by means of publicly published regular annual reports of ten banks operating in the Republic of Serbia and quarterly reports of the National Bank of Serbia, in order to define the relationship between the movements of the listed components. As the participation of the 10 largest banks according to the criterion of the amount of the balance sheet assets is 44% to 77%, the average values of their performances largely approximate the performances of the entire banking system of the Republic of Serbia.